Issues and challenges: preparation as a school counsellor - Syed Mahmood, Syarifah Rohaniah; fadzir, farah azira; Ismail, Halim; Ssekamanya, Siraje Abdallah; Ahmad, Noorlila (Asian Scholars Network, 2025)
Fresh graduates often face significant challenges in preparing for entry into the professional workforce. The transition from academic life to the workplace is particularly important for final-year students, as it signifies a pivotal stage in their personal and professional development. To investigate this transitional period, a phenomenological approach was adopted to explore the challenges experienced by final-year undergraduates during their internships. In-depth interviews were conducted with four female students from a Public Institution of Higher Education (PIHE) located in Klang Valley, Kuala Lumpur, Malaysia. The data collected were analysed using thematic analysis, which identified five distinct categories of challenges faced by the participants: adjustment to the school environment, unsupportive working environment, professional issues, struggling with main duties and additional duties.